Examining Secondary Special Education Teachers' Literacy Instructional Practices. Issue 1 (2nd January 2017) - Leko, Melinda M.; Handy, Tamara; Roberts, Carly A.
ABSTRACT: This study presents findings from a survey of secondary special education teachers who teach reading. Respondents were 577 special education teachers from a large Midwestern state who completed an online or mail survey. Results based on quantitative and qualitative analyses indicate predominant foci of secondary special education teachers' reading instructional practices were teaching vocabulary and comprehension, engaging in ongoing formative assessment, and incorporating technology into instruction. Major themes included the widespread use of commercial reading programs and a bifurcation of instructional roles. These findings are discussed in relation to the national discourse on adolescent literacy and current schooling initiatives including the Common Core State Standards and Multi-tiered Systems of Support.